Kahden taalarin raha - Ingman, A. E. (Alfred Emil), 1860-1917 (Salt Lake City, UT : Project Gutenberg, 2015)
"Kahden taalarin raha" by A. E. Ingman is a novel written in the early 20th century. The story is set in Finland and follows the life of a young protagonist navigating the challenges of adulthood after losing his mother. He takes on a role in his uncle$1 (Bs fishing household and soon becomes engrossed in aspirations of adventure and the mysteries that surround the Muklaren islands. At the start of the tale, the narrator reflects on his childhood and the local legends surrounding the Muklaren islands, mysterious places that spark both fear and curiosity. After the death of his mother, he is left alone, but fortunate to have his uncle who employs him in fishing. The narrator introduces his cousin, Tom, a spirited boy who dreams of adventures on the high seas, including a fateful expedition to the Muklaren islands. As preparations for a fishing trip unfold amidst familial duties and local lore, the stage is set for adventures intertwined with elements of myth, exploration, and the realities of life on the coast. (This is an automatically generated summary.)s
Release date is 2015-01-03
Produced by Tapio Riikonen
Keywords: Seafaring life -- Juvenile fiction